STUDI TENTANG TOKSOPLASMOSIS PADA PASIEN KUCING DI RUMAH SAKIT HEWAN PROF. SOEPARWI YOGYAKARTA - , BERNADETE MIRACLELITA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toxoplasmosis is an obligate-intracellular protozoal disease caused by Toxoplasma gondii. This parasite occurs worldwide with variative prevalence, infecting all warm-blooded vertebrates, including humans. Cats are the only definitive host that are capable of excreting oocyst into the environment. As a pet animal, cats increase the risk of transmission, especially to humans, if they are not properly treated. The aim of this study is to measure the infection rate of toxoplasmosis in cats patients of Prof. Soeparwi Animal Hospital Yogyakarta, and also to compare the differences in erythrocytes, Hb, PCV, and leucocytes count between the seropositive and seronegative cats. Forty blood samples are collected through the cephalic or femoral vein, 1cc in the EDTA tube for the blood count and 2cc remains in the syringe for the serological test. Serological test is done using the Pastorexï Toxo Kit resulting 4 of 40 (10%) cats are seropositive to T. gondii. Total erythrocytes count, Hb, and PCV level are insignificantly (P>0.05) lower in seropositive cats, and total leucocytes count levels are insignificantly (P>0.05) higher in seropositive cats. It can be concluded that cats, particularly patients of Prof. Soeparwi Animal Hospital Yogyakarta, have actually low potential of being a reservoir for toxoplasmosis.